RESTORATIVE JUSTICE APPROACH TO CORPORATE PERPETRATORS OF ENVIRONMENTAL CRIMES BASED ON NATIONAL LEGAL IDEALS - Jeremia Sipahutar; Prija Djatmika; Lilik Mulyadi (CV. RADJA PUBLIKA, 2025)
Indonesia is a state based on the rule of law, placing law as one of the instruments for the state to uphold its national ideals and as a means to achieve justice, certainty, and benefit for all members of society. This study examines the application of restorative justice in addressing corporate environmental crimes within Indonesia’s legal framework. Although the National Criminal Code (KUHP Nasional) recognizes both individuals and corporations as legal subjects and acknowledges restorative justice, its implementation in environmental law enforcement remains limited. Law Number 32 of 2009 on Environmental Protection and Management still prioritizes a retributive approach, restricting the use of restorative mechanisms in corporate environmental offenses. Using a normative legal research method, this study analyzes statutory provisions and theoretical frameworks to explore the possibility of integrating restorative justice into corporate liability. The findings highlight the need for legal reforms to align environmental law enforcement with national legal ideals, particularly Pancasila. Incorporating restorative justice in corporate environmental crimes would emphasize remediation, victim compensation, and community involvement, ensuring a balance between legal certainty, justice, and environmental sustainability.